A numerical investigation of Vortex-Induced Vibration response characteristics for long flexible cylinders with time-varying axial tension. (February 2018) - Yuan, Yuchao; Xue, Hongxiang; Tang, Wenyong
Abstract: Vortex-Induced Vibration (VIV) for flexible cylinders is a typical fluid–structure interaction problem, and it becomes more complex when the time-varying axial tension effect is considered. An available force–decomposition model is proposed in this paper to investigate the cross-flow VIV response characteristics with time-varying tension. VIV hydrodynamic forces are all based on forced vibration experimental data, and structural stiffness will be updated at each time step to take the tension variation into account. Firstly, this VIV model is compared against the published experimental results of a small-scale cylinder with constant and time-varying tensions. Next, 60 cases of a long flexible cylinder are designed to investigate the time-varying tension effect comprehensively. Several new phenomena such as amplitude modulation, time-lag, frequency transition, mode jump and multi-frequencies response superposition are captured in the response comparison with the constant tension case. The effects of initial phase, amplitude and frequency of the varying tension are respectively discussed in detail. The Mathieu-type resonance between VIV and time-varying tension excitation is proved existent. The response displacement and strain will enlarge significantly at ω T = 2 ω C T, to which enough attention needs to be paid. Highlights: A VIV model for flexible cylinders with time-varying axial tension is proposed. The proposed numerical model is compared with laboratory experiments. New phenomena like mode jump and multi-frequency superposition are found. 60 designed time-varying axial tension cases are simulated. Mathieu-type resonance is captured at ω T = 2 ω C T .